1996
DOI: 10.1007/s002130050145
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the calcium channel blocker nimodipine on nicotine-induced locomotion in rats

Abstract: The effects of nimodipine, an L-type calcium channel antagonist, on nicotine-induced locomotor activity were investigated in drug-naive rats. Nicotine (0.4 mg/kg i.p.) produced significant increases in locomotion following acute administration. However, when rats were given injections of nimodipine (5, 10, or 20 mg/kg i.p.) 1 h prior to the test drug, nicotine-induced locomotor activity was altered. Nimodipine 5 mg did not significantly block locomotor activity produced by nicotine. In contrast, pretreatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…3a, b). Studies based on alcohol and nicotine withdrawal protocols show that nimodipine is able to reduce the resultant locomotor hyperactivity (Hart et al 1996;Watson and Little 2002). However, it is difficult to compare the results from previous studies with those of the present study because studies showing the effects of nimodipine in non-treated animals are very scarce.…”
Section: Discussionmentioning
confidence: 60%
“…3a, b). Studies based on alcohol and nicotine withdrawal protocols show that nimodipine is able to reduce the resultant locomotor hyperactivity (Hart et al 1996;Watson and Little 2002). However, it is difficult to compare the results from previous studies with those of the present study because studies showing the effects of nimodipine in non-treated animals are very scarce.…”
Section: Discussionmentioning
confidence: 60%
“…This was later confirmed by chronic nicotine treatment for 7 days in mice that led to an increase in Ca v 1.2 and Ca v 1.3 protein levels in the cortex [341]. Behaviorally, LTCC blockers have been shown to attenuate acute nicotine-induced locomotor activity (nimodipine [315]), as well as decrease the development (nimodipine, verapamil, diltiazem [316]) and expression (nimodipine, verapamil, diltiazem, nifedipine [16,316]) of nicotine behavioral sensitization. Similarly, treatment with nimodipine, diltiazem, and verapamil reduced the rewarding effects of nicotine using CPP [316].…”
Section: Nicotinementioning
confidence: 81%
“…Reduced chronic alcohol-induced seizures [313] Nifedipine and nimodipine [314] Nicotine Locomotor activity Nimodipine Reduced acute nicotine induced locomotor activity [315] Behavioral sensitization; Locomotor activity Nimodipine, verapamil and diltiazem Suppressed development and expression of behavioral sensitization [316] Nifedipine [16] consumption [301][302][303][304], and nifedipine, verapamil, and diltiazem decrease the heightened locomotor activity induced by low doses of ethanol [301,307,308]. In contrast, a study reported that nifedipine and verapamil had no impact on the ethanol-induced increase in locomotor activity [309], nor did isradipine, nifedipine or nimodipine on ethanol consumption [305,306].…”
Section: Nifedipinementioning
confidence: 99%
“…Calcium influx through LTCCs is an attractive mechanism for nicotine-dependent calcineurin activation because these calcium channels are critical for several nicotine-mediated behaviors. LTCC antagonists block acute nicotine-dependent locomotor activation and attenuate chronic nicotine-mediated locomotor sensitization (Hart et al, 1996;Biala, 2003). In addition, chronic nicotine administration increases the expression of various LTCC subunits in the cortex (Hayashida et al, 2005).…”
mentioning
confidence: 99%